Developing a web-based simulator for safety management system training - Direstu Amalia; Wildan Nugraha; Dwi Cahyono; Virma Septiani; Rio Rizko; Rakha Racahyo; Alfian Yudiansyah; Dwi Lestary (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
ICAO document 9859 mandates that six stakeholders in its member countries are required to implement a Safety Management System (SMS). The support of all personnel in the organization's efforts to achieve aviation safety must be supported by safety management training. The implementation of online SMS training provides a pedagogical challenge for the instructor, so, methods are needed to stimulate the 4Cs: critical thinking, creativity, communication, and collaboration. These challenges must be faced, one of which is using a simulator media that has pedagogical advantages that not only help teachers but are also expected to provide a more realistic learning experience. This research has succeeded in implementing a web-based Hazard Identification and Risk Assessment (HIRA) application product that is integrated with safety reporting and can be accessed by all students. The product presents tables and graphs that are used as evidence of formal processes in safety documentation and safety monitoring activities with real conditions in the field. This product also has a General Risk Assessment Process simulation feature that can be used for risk mapping activities for training participants as well as standardized presentation materials. The results of the user experience test show a positive response with an average value above 0.8, representing an application's pragmatic and hedonic aspects.